Eye-tracking device for disabilities - Wong, Wei Jun (Nanyang Technological University, 2020)
This project aims to build a mobility device to aid mobility-impaired people and improve their quality of life. From my research, everyday there are an average of 15 new people suffering from amyotrophic lateral sclerosis (ALS). This disease causes them to lose their ability to walk/move around but allow them to retain the function of their eyes, This project will enable users to control the mobility device using their eyes, this will allow them to move their head with minimal to no support. There are two parts in this project: hardware and software. The hardware consists of a headset, eye tracking glasses, arduino UNO and servo motors. The software consists of machine learning using both arduino, processing and Microsoft visual studio with OpenCV. The user will wear the headset with the eye tracking glasses, pitch and yaw of the eye tracking glasses is controlled by two servo motors. Code input into the arduino software will run the servo motors and a graphic user interface (GUI) created using processing will allow the user to click on the respective button and control the servo motors. Eye tracking will be done using Microsoft visual studio program. By implementing the eye tracking software and the GUI, we can control the servo with our eyes. Improvement can still be made to this project and recommendation have been input in it.